Pengaruh Penyuluhan Hand Hygiene Terhadap Kepatuhan Kebersihan Tangan Pada Siswa SDN Ciranji Tahun 2025: The Effect of Hand Hygiene Education on Hand Hygiene Compliance Among Students at SDN Ciranji in 2025 - Nia Khusumawati; Solehudin; Sancka Stella G. Sihura (MPI Press, 2026)
Introduction: Handwashing behavior is one of the most effective actions to prevent diseases, especially in elementary school environments, however, student’s compliance in proper handwashing remains low. Therefore, educational efforts such as the WHO six-step handwashing health education are necessary. Objectives: To determine the effect of WHO six-step handwashing health education on handwashing compliance among students at SDN Ciranji in 2025 Method: This study used a one group pretest-posttest design. The sample consisted of sixth-grade students at SDN Ciranji selected using a total sampling technique. Data were analyzed using univariate analysis to describe the frequency distribution of respondents’ characteristics and handwashing compliance levels before and after the health education. A normality test was conducted to determine the appropriate statistical test for bivariate analysis. Since the data were not normally distributed, the Wilcoxon test was used to determine differences in compliance before and after the health education. Result: The results showed an increase in students’ handwashing compliance scores after the health education was given. The Wilcoxon test result showed a p-value of 0.001 (< 0.05), indicating that the WHO six-step handwashing education had a significant effect on handwashing compliance among students at SDN Ciranji Conclusion: The results showed an increase in students’ handwashing compliance scores after the health education was given. The Wilcoxon test result showed a p-value of 0.001 (< 0.05), indicating that the WHO six-step handwashing education had a significant effect on handwashing compliance among students at SDN Ciranji